Hållbar Spedition – Balansen mellan miljö och ekonomi - Bursjöö, Martin; Gabrielsson, Johan (My University, 2012)
This bachelor’s thesis is a market analysis and study of the transportation market that focuses on the opinions regarding environmentally friendly transports and whether it is profitable conducting this type of business. The central issue in this work has been; "Is it possible to carry out profitable freight forwarding, while still focusing on environmental issues?" With the help of literature studies and interviews, we have built a well-founded understanding of the overall mindset of the industry. The gathering of information is the basis for the theory that we present, which in turn is the basis for the analysis section The study examines whether there is opportunity to influence the company's way of thinking and taking action related to transportation by raising a discussion. The report concludes that it is in fact possible to carry profitable freight forwarding, while still focusing on environmental issues. There are many examples that prove this, but it requires dedication, willpower and determination on all levels, individual-, organizational- and systematical levels
Keywords: Maskinteknik; Farkostteknik; Transport; Mechanical Engineering; Vehicle Engineering; Transport